Ash Cooler Heat Recovery Under Energy Conservation Scheme - Vikash R Gupta; Lalatendu Pattanayak (International Journal of Applied Power Engineering (IJAPE), 2014)
A healthy fluidization state in circulating fluidized-bed combustion (CFBC) combustor is attributed to proper quantity of hot bed material (ash), which acts as a thermal fly-wheel. It receives & stores thermal energy from the burning of fuel (lignite) & distributes uniformly throughout the combustor & helps in maintaining a sustained combustion. The quantity of bed ash inside the combustor or size of the bed, depends upon boiler load & subsequently upon combustor temperature, lignite feed rate and ash % in lignite. As these parameters varies during process continuously, sometimes it becomes necessary to drain out the ash from the combustor. As & when differential pressure across the bed is increased from a justified level, draining of hot bed ash starts into Ash Coolers. Bed ash is drained at very high temperature of 850 oC & it also contains burning particles of lignite. This paper describes the heat recovery from bed ash, unloaded from the combustor into ash cooler, by pre-heating the condensate water of turbine cycle in a 125 MW CFB boiler of Surat Lignite Power Plant in India. The thermal performance of ash cooler was derived by doing a heat balance calculation based on the measured temperature of ash and cooling water with different load. From the heat balance calculation influence of ash temperature and ash amount on heat transfer coefficient is determined. Simulation is carried out around main turbine cycle indicates improved thermal economy of the unit, higher plant thermal efficiency, lower plant heat rate and reduce fuel consumption rate. Also simulation result shows that the heat transfer coefficient increase with ash amount and decreases with increase in ash temperature.